Experimental and numerical investigations of thermal and flow characteristics of a shear-thinning non-Newtonian fluid in a differentially heated cavity. (15th May 2022) - Pandey, Sudhanshu; Yoon, Sang Youl; Balachandar, S.; Ha, Man Yeong
Highlights: The thermal and flow characteristics of carboxymethyl cellulose are investigated by experimental and numerical means, in order to assess the shear-thinning behaviour of a non-Newtonian fluid inside a differentially heated square cavity. The present experimental results can be used as benchmark for validation of numerical simulations of non-Newtonian fluids. Of the three alternative models, the carreau model is the most effective, and is capable of predicting the thermal and flow performances within the thermal system described here with precision. Abstract: The thermal and flow characteristics of carboxymethyl cellulose (CMC) were investigated by experimental and numerical means, in order to assess the shear-thinning behaviour of a non-Newtonian fluid inside a differentially heated square cavity. A novel particle image velocimetry technique was used to analyse natural convective flow in a non-Newtonian fluid. The square cavity was filled with an aqueous solution of CMC, which exhibits non-Newtonian shear-thinning behaviour. The present study carried out a comparative analysis of several different numerical models, including the Power-law model, the Cross model, and the Carreau model, with the aim of producing a model that can be used to approximate viscosity distributions for non-Newtonian fluids. Three Rayleigh numbers were considered, Ra=1.22 × 10 4, 2.29 × 10 4, and 3.33 × 10 4 . The patterns and magnitudes of velocity obtained from the experimental and numerical analyses were in close agreement in the proximity of the cavity walls and at the core of the natural convective flow. For CMC, the mean Nusselt number (Nu) showed a direct correlation with Ra. The outcomes provide some confidence in terms of their use as benchmark data for the simulation of a non-Newtonian fluid medium. For the first time, the proposed system was applied to non-Newtonian shear-thinning (pseudoplastic) flow, and quantities such as the distribution of mean Nu along the hot wall and the velocity field were determined concurrently for different Rayleigh numbers. Of the three alternative models, the Carreau model is the most effective, and is capable of predicting the thermal and flow performances within the thermal system described here with precision. Graphical abstract: Image, graphical abstract